The model of the dependence of the abrasive wear value on the maximal linear wear - Вишневський, О.А. (Proceedings of National Aviation University (archive), 2012)
The relation of the contact area of the rubber roll with a sample and the maximal linear wear value is found. The mathematical model of the dependence of the wear volume weight value on the maximal dimple depth is presented with the friction on abrasive particles fixed nonrigidly. The relation of volume weight wear with the rubber roll contact surface area with a sample with the friction on abrasive particles fixed nonrigidly is established.